STUDI TENTANG PERENCANAAN PROGRAM BIMBINGAN DAN KONSELING YANG DILAKUKAN OLEH GURU PEMBIMBING DI SMP NEGERI KECAMATAN MUNGKA KABUPATEN 50 KOTA - Alista, Delza Anggilia; Kasih, Fitria; Gusneli, Gusneli (Bimbingan dan Konseling, 2013)
This research is motivated by the planning guidance and counseling program conduct counselor. Based on the initial survey found a tutor is not planning guidance and counseling programs to suit the needs of learners (need assessment). This study aimed to look at how planning guidance and counseling program conducted by the counselor at the SMP Negeri Kecamatan Mungka Kabupaten 50 Kota, with the limitation of the research problems are: 1) The form of the preparation of planning guidance and counseling program conducted by the counselor views of learners needs 2) form of planning guidance and counseling program conducted by the counselor views of determination means, personnel / division of labor. This type of research is qualitative research. This study takes a guidance counselor at SMP Negeri Kecamatan Mungka Kabupaten 50 Kota as research informants. The Data were collected through interviews and documentation of the planning guidance and counseling program. The findings of the study revealed that planning guidance and counseling program conducted by the counselor is still lacking, due to the lack of existing infrastructure in schools, lack of creativity in finding a tutor learner needs, the lack of instrumentation applications that are used to determine the needs of the students and lack of support from school personnel in planning guidance and counseling program. Based on the research results to the counselor recommended interested parties will be expected to be able to use instrumentation application guidance and counseling to determine the needs of the students in planning a program appropriate guidance and counseling needs of the students, are expected to renew a program that fits the needs of learners every year, and personnel in the school are expected to be working in planning guidance and counseling programs to suit the needs of learners.